Agriculture in 2040 according to the European Commission Communication “A Vision for Agriculture and Food” - Niewiadomska, Agata (Przegląd Prawa Rolnego, 2025)
This article aims to evaluate the legal solutions proposed in the European Commission’s Communication “A Vision for Agriculture and Food.” This Communication marks the beginning of the discussion on the new Common Agricultural Policy after 2027, setting out a vision of its development until 2040. It sets out plans for an agricultural system that will be attractive, competitive, sustainable and fair for current and future generations. The Communication contains several proposals that focus in particular on placing research, innovation, knowledge and skills at the heart of the European agri-food economy. It also identifies the challenges that Polish agriculture and agricultural law will have to face. The article assesses potential legal changes relating to the shaping the European Commission’s vision for agriculture and food.